Lecture 11 - Spline curves (slides)

Reversing the de casteljau algorithm graphics lecture

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: phics Lecture 11: Slide 30! Four point Bezier Curves and Cubic Patches Four point Bezier Curves and Cubic Patches " •  We can show their equivalence:
 ! We can show their equivalence: Four point Bezier curve = Cubic patch going through the first and last knots (P0 and P3 ) It is possible to show their equivalence by •  It is possible to show their equivalence by ! I Expanding the iterative blending equation ! –  Expanding the iterative blending equation I Reversing the de Casteljau algorithm ! –  Reversing the de Casteljau algorithm Graphics Lecture 11: Slide 31! 31 / 38 Expanding the blending equation Expanding the blending equation Expanding of fourblending equation " the knots we can Expanding the blending equationexpand the Bernstein blending For the case Forfunction to get a knots we can expand the Bernstein blending For the case of four knots we can expand the Bernstein blending the case of four polynomial in µ: function to get a polynomial in µ::we can expand the Bernstein •  For to get a polynomial in µ function the case of four knots 3 X blending3 function to get a polynomial in µ: ! X P(µ) = 3 X W (3, i, µ)Pi P(µ) = W (3, i, µ)P P(µ) = iW (3, i, µ)Pii =0 ii=0 ==0(1 3µ)3 P0 + 3µ(1 2µ)2 P1 +23µ2 (1 µ)P2 + µ3 P3 = (1 µ) 3P0 + 3µ(1 µ) 2P1 + 3µ 2(1 µ)P2 + µ3 P3 = (1 µ) P0 + 3µ(1 µ) P1 + 3µ (1 µ)P2 + µ3 P3 •This can multiplied outoutout give equation of the the form:   Thisbe bebe multiplied giveto giveequation of form: can multiplied to to an an an equation of the This can be multiplied out to give an equation of the form: This can form: ! P(µ) = a3 µ3 + a2 µ2 + a1 µ + a0 P(µ) = a3 µ3 + a2 µ2 + a1 µ + a0 P(µ) = a3 µ3 + a2 µ2 + a1 µ + a0 where ! w where here a0 = P 0 where a0 = P 0 a0 a = = 0 3 P P 3P0 1 1 a 1 = 3 P 1 3P0 a1 a = = P3P 3P6P + 3P 31 0 2 2 1 0 a 2 = 3 P 2 6P1 + 3 P 0 a2 a = = PP 6PP++PP 32 3 1 2 3 3 0 1 P0 3 3 a3 = P3 3P2 + 3P1 P0 a3 = P3 3P2 + 3P1 P0 32 / 38 Expanding the blending equation Expanding the blending equation " Expanding the blending equation These equations are linear These equations are linear •  These equations are a linear ! P 0= 0 ! a0 = P 0 3 P a= 1 ! ! a1 = a2 a2 = a 1 3P0 3 P 1 3 P P0 6P + 3 P 3 = 2 1 0 3P2 6P1 P 3+ 0 P 3+2 P 3 1 P0 3 = P3 a3 = P3 3P2 + 3P1 P0 Note that P0 P a P3 are the endpoints •  Note that P0 and and re the endpoints! NoteRecallP0 and P33 are the endpoints that the matrix form used for a cubic spline •  Recall the matrix form used for a cubic spline patchpatch ! Recall the matrix form used for a cubic spline patch ! 0 10 10 1 a 1 0 0 10 P 0 10 0 0 10 B a0 a1 C B 0 1 01 00 0 0 C B P0 C P0 BC C = B CB C0 C B a1 a A @ 3 @C 2 B 0 12 0 3 C1 A @ C 3 A 0 C B P0 P B B0 =B @ a2 A @ 3 2 21 3 2 A 1 P3 A 0 1@ a3 P3 a3 2 1 2 1 P0 3 Graphics see Lecture 11: Slide 33! see 33 / 38 Expanding the blending equation Expanding the blending equation " Expanding the blending equation These equations are linear These equations are linear •  These equations are = P! a0 linear 0 ! a0 = PP a = 30 1 ! ! 3P0 3P0 + 3 P 6P 3 P1 3 P2 1 0 3P2 36P1+ 33P0 P P3 P2 + P1 3 0 a3...
View Full Document

This document was uploaded on 03/26/2014.

Ask a homework question - tutors are online